Successful talent transfer of German elite athletes: reasons and mechanisms - an interview study - Siener, M.; Schmid, L.; Vogt, T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In competitive sports, nations have an increased interest in identifying and developing talented athletes. However, only a handful of these gifted individuals make it to the top. This situation poses a challenge, especially for smaller countries with a potentially limited pool of promising athletes or budget. A talent transfer—meaning the transfer of already (semi)successful athletes to another sport—can be an opportunity to convert the support already made, ideally into a medal. However, clubs and associations often hesitate to release their athletes, having invested significant time and resources in them, which is not always in the interests of the athletes. Therefore, this study aims to identify motives and circumstances with a positive influence for a successful talent transfer. METHODS: A total of seven German athletes (25±2 years; n*=4) who had changed sports during their career were asked about their talent transfer using a guided interview. All participants are currently professional athletes, part of their national teams, and regularly compete internationally. The interviews focused on reasons for the switch, the transfer process, encountered challenges, differences between the original and new sports, and available support. The transcribed interviews were then analyzed using MAXQDA. RESULTS: Interviewed athletes from the sports of gymnastics, athletics, volleyball, and swimming transitioned to pole vaulting, bobsledding, triathlon, rowing, or ski freestyle aerials at an average age of 19. Common reasons for switching included lack of motivation, enjoyment, or prospects for international success in their original sport. The athletes emphasized an importance of family support and noted similar physiological demands in the switched-to sport being helpful. Technical challenges were mitigated through gentle introduction with less pressure. The athletes supported a talent transfer but expressed concerns about the absence of organized programs in Central Europe and pointed in particular to the lack of support from clubs and associations for athletes switching sports. CONCLUSION: Overall, there are a variety of possible reasons for a positive talent transfer. However, according to the athletes interviewed, similar physical abilities and a basic understanding of the fundamentals of the target sport appear to be crucial for a successful talent transition. Other studies show, such alignment can lead to rapid performance improvements, further endorsing successful talent transfers (Cury et al., 2022, doi: 10.1080/23750472.2022.2033638). In addition, there are already confirmed motivational and psychological effects that can ultimately be the cause of making a talent transfer (MacNamara, & Collins, 2015, doi: 10.1080/02640414.2014.908324). Although there are already promising talent development programs in Australia and Canada, the extent to which these can also be established in Germany and prevail against internal club interests remains to be investigated.